«Credo quia absurdum est». Ещё раз о рельефах из Кубачи - Доде, З.В. (Степи Европы в эпоху средневековья, 2012)
This paper is the author’s polemic answer to M.M. Mammaiev and A.A. Ivanova's article “On attribution of medieval Kubachi stone reliefs" which claims to be a scientific review of Z.V. Dode's book “Kubachi reliefs. A new view on ancient stones”. The author gives reasons for her fundamental disagreement with M.M. Mammaiev and A.A. Ivanova’s arguments which methodically follow the tradition of autochthonism, a dominating trend in the Soviet historical science. This trend implied studying the originality and uniqueness of national culture as a focus of research. In Z. V.Dode’s opinion, the acknowledgement of the Dagestan reliefs as an isolated cultural phenomenon leads to insurmountable difficulties in interpretation since both the Kypchaks and the Mongols are shown on reliefs along with the Dagestanis. The author believes that the scenes on the stone reliefs are indicative of not the regional, but the imperial scale of processes in which the medieval Zirikhgeran, which is nowadays known under the Turkic name “Kubachi”, was involved.